Carbon nanotube/Co3O4 nanocomposites selectively coated by polyaniline for high performance air electrodes - Jin Young Kim (Nature Portfolio, 2017)
Abstract We herein report the preparation of carbon nanotube (CNT)/Co3O4 nanocomposites selectively coated with polyaniline (PANI) via an electropolymerization method, for use as an effective electrode material for Li-air (Li-O2) batteries. The Co3O4 catalyst attached to the CNTs facilitated the dissociation of reaction products and reduced the overpotential of the cells. As the carbon surface activates the side reactions, the PANI coating on the carbon surface of the electrode suppressed the side reaction at the electrode/Li2O2 and electrode/electrolyte interfaces, thus enhancing the cycle performance of the electrode. In addition, the catalytic activity of Co3O4 on the CNT/Co3O4 nanocomposites remained unaffected, as the Co3O4 surface was not covered with a PANI layer due to the nature of the electropolymerization method. Overall, the synergic effect of the PANI layer and the Co3O4 catalyst leads to a superior cyclic performance and a low overpotential for the electrode based on selectively PANI-coated CNT/Co3O4 nanocomposites.